2(k-4)=6

Simple and best practice solution for 2(k-4)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(k-4)=6 equation:


Simplifying
2(k + -4) = 6

Reorder the terms:
2(-4 + k) = 6
(-4 * 2 + k * 2) = 6
(-8 + 2k) = 6

Solving
-8 + 2k = 6

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2k = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 2k = 6 + 8
2k = 6 + 8

Combine like terms: 6 + 8 = 14
2k = 14

Divide each side by '2'.
k = 7

Simplifying
k = 7

See similar equations:

| 11p=5p+2(10p-7) | | x*x+2*x+9=0 | | 2x=78+1 | | 2a/18ab | | h=-4.9t^2+50t+80 | | x*x*x*4+93*x*x+200*x+1000=0 | | -4(-7x+8)=-32 | | 2x+39=x-10 | | 4x-16=15x | | Z^2+2z+1=2i | | 4x^2+5=53 | | -10=-7x-17/8 | | 0.3=p-250 | | 10y=-5x+12 | | 4y+8y=180 | | 13/r=-12/13 | | -6x+7=7x-19 | | 3=a/5-9 | | 4x+7(-4x-28)=20 | | 19y+43=81 | | -824=8(-15x+2) | | 7-2.59= | | -154=-8r-10 | | 3(t+4)-2(2*t+3)=-4 | | -12n+25=-14 | | A+a+a+60=180 | | 7x-17=2x-2 | | -10x+355=-163-3x | | 4x-13=1+x-4 | | 3x+4i=6-2yi | | (5x^4*y^4+28x^6)dx+(4x^5*y^3-3y^2)dy=0 | | -11=4(-2)-3 |

Equations solver categories